RESEARCH ON STRESS ANALYSIS OF PINNED CONNECTION BASED ON PHOTOELASTIC EXPERIMENT - QU FuZheng; WANG Qi; ZHANG ChunGuang; PAN DeGuo; XIE ZhengYi (Jixie qiangdu)
There are no rules and standards relating to the calculation of pinned connection because of its partial structure and internal stress state are very complex. In the design of pinned connection,great strength reserves are chosen to compensate for the lack of calculation accuracy. The typical pinned connection in the crawler crane luffing tension plates was took as the research object,based on similarity theory,the distorted model photoelastic experiment was conducted to study the mechanical behavior of pinned connection and the stress state of tension plates. Based on the results of pinned connection in the tension plate,Setting algorithm parameters of finite element,the results can be used as a reference in the designing and checking of pinned connection.